Nondipole Effects in Atomic Ionization Induced by an Intense Counter-Rotating Bicircular Laser Field - Kahvedzic, Resad; Habibovic, Dino; Becker, Wilhelm; Gräfe, Stefanie; Milosevic, Dejan B. (Annalen Der Physik, 2023)
Nondipole effects occurring in the process of atomic ionization by an intense, mid-infrared, counter-rotating bicircular laser field are investigated using the strong-field approximation with leading-order nondipole corrections. The time integrals appearing in the expression for the differential ionization rate are computed in two ways: numerically, and by applying the saddle-point approximation. The nondipole corrections introduce an asymmetry in the photoelectron momentum distribution along the field propagation direction. The asymmetry is quantified by the partial average value of the propagation-direction momentum component of the photoelectrons and by the normalized difference of the differential ionization rates computed including and excluding the nondipole corrections. Using the saddle-point approximation, it is investigated how the nondipole corrections change the solutions for direct photoelectrons and how this affects the momentum spectra. The impact of nondipole corrections increases with increasing photoelectron energy. Analysis of the complete photoelectron spectra including both direct and rescattered photoelectrons shows that, in the low-energy region, a shift against the propagation direction occurs. The partial average of the propagation–direction momentum component in the rescattering region exhibits a plateau structure and also a local minimum structure that was recently observed in an experiment with a linearly polarized laser field (Lin et al., Phys Rev. Lett. 128, 023201 (2022)).
CRIS-Team Scopus Importer:2023-04-20
Keywords: nondipole effects; strong-field ionization; tailored laser fields